2020
DOI: 10.1136/bmjophth-2019-000304
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated risk factors of diabetic retinopathy and macular oedema in patients recently diagnosed with type 2 diabetes

Abstract: ObjectiveTo determine the prevalence of diabetic retinopathy (DR) and diabetic macular oedema (DME) and their associated risk factors in patients recently diagnosed with type 2 diabetes.Methods and analysisWe carried out a cross-sectional study from April 2014 to August 2017. We included patients aged ≥18 years. Diabetes was defined as fasting plasma glucose of >7.8 mmol/L or 2-hour postload plasma glucose of >11.1 mmol/L. Non-mydriatic fundus examination with a digital-fundus camera was performed. Three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 43 publications
(37 reference statements)
0
21
0
3
Order By: Relevance
“…Interestingly, it has been shown that supplemented SPP1 inhibits experimentally induced osmotic swelling in ex vivo rat RMG ( Wahl et al, 2013 ). Glial swelling is involved in pathology of diabetic macula edema, a severe complication of DR ( Coughlin, Feenstra & Mohr, 2017 ; Daruich et al, 2018 ; Graue-Hernandez etal., 2020 ; Wahl et al, 2013 ). We speculate that a decrease in SPP1 expression level might contribute to RMG swelling in diabetic macular edema.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, it has been shown that supplemented SPP1 inhibits experimentally induced osmotic swelling in ex vivo rat RMG ( Wahl et al, 2013 ). Glial swelling is involved in pathology of diabetic macula edema, a severe complication of DR ( Coughlin, Feenstra & Mohr, 2017 ; Daruich et al, 2018 ; Graue-Hernandez etal., 2020 ; Wahl et al, 2013 ). We speculate that a decrease in SPP1 expression level might contribute to RMG swelling in diabetic macular edema.…”
Section: Discussionmentioning
confidence: 99%
“…The worldwide prevalence for diabetes in adults is increasing and is predicted to exceed ten percent of world population by 2040 ( Ogurtsova et al, 2017 ). Diabetic retinopathy (DR) is a severe and frequent comorbidity of diabetes and a leading cause of vision loss ( Ducos et al, 2020 ; Graue-Hernandez etal., 2020 ; Leasher et al, 2016 ). However, the underlying pathomechanisms remain to be comprehensively elucidated ( Mesquida, Drawnel & Fauser, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it has been shown that supplemented SPP1 inhibits experimentally induced osmotic swelling in ex vivo rat RMG (Wahl et al 2013). Glial swelling is involved in pathology of diabetic macula edema, a severe complication of DR (Coughlin et al 2017;Daruich et al 2018;Graue-Hernandez et al 2020;Wahl et al 2013). We speculate that a decrease in SPP1 expression level might contribute to RMG swelling in diabetic macular edema.…”
Section: Discussionmentioning
confidence: 85%
“…The worldwide prevalence for diabetes in adults is increasing and is predicted to exceed ten percent of world population by 2040 (Ogurtsova et al 2017). Diabetic retinopathy (DR) is a severe and frequent comorbidity of diabetes and a leading cause of vision loss (Ducos et al 2020;Graue-Hernandez et al 2020;Leasher et al 2016). However, the underlying pathomechanisms remain to be comprehensively elucidated (Mesquida et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Aunque el tamaño de muestra no fue amplio, la proporción de pacientes diabéticos que presentó retinopatía diabética fue semejante a la reportada por otros estudios en nuestra población (27 vs. 17.3% 13 ) y en poblaciones de otros países 14,15 . A pesar del tiempo y las estrategias utilizadas para el control de la enfermedad, no se ha logrado disminuir la frecuencia de esta complicación; sin embargo, sí se ha reportado una disminución en la frecuencia de casos con lesiones que pongan en riesgo la función visual 16,17 .…”
Section: Discussionunclassified